High urinary homoarginine excretion is associated with low rates of all-cause mortality and graft failure in renal transplant recipients - Frenay, Anne-Roos S; Kayacelebi, Arslan Arinc; Beckmann, Bibiana; Soedamah-Muhtu, Sabita S; de Borst, Martin H; van den Berg, Else; van Goor, Harry; Bakker, Stephan J. L; Tsikas, Dimitrios (Amino acids, 2015)
Renal transplant recipients (RTR) have an increased cardiovascular risk profile. Low levels of circulating homoarginine (hArg) are a novel risk factor for mortality and the progression of atherosclerosis. The kidney is known as a major source of hArg, suggesting that urinary excretion of hArg (UhArg) might be associated with mortality and graft failure in RTR. hArg was quantified by mass spectrometry in 24-h urine samples of 704 RTR (functioning graft ≥1 year) and 103 healthy subjects. UhArg determinants were identified with multivariable linear regression models. Associations of UhArg with all-cause mortality and graft failure were assessed using multivariable Cox regression analyses. UhArg excretion was significantly lower in RTR compared to healthy controls [1.62 (1.09–2.61) vs. 2.46 (1.65–4.06) µmol/24 h, P < 0.001]. In multivariable linear regression models, body surface area, diastolic blood pressure, eGFR, pre-emptive transplantation, serum albumin, albuminuria, urinary excretion of urea and uric acid and use of sirolimus were positively associated with UhArg, while donor age and serum phosphate were inversely associated (model R ² = 0.43). During follow-up for 3.1 (2.7–3.9) years, 83 (12 %) patients died and 45 (7 %) developed graft failure. UhArg was inversely associated with all-cause mortality [hazard risk (HR) 0.52 (95 % CI 0.40–0.66), P < 0.001] and graft failure [HR 0.58 (0.42–0.81), P = 0.001]. These associations remained independent of potential confounders. High UhArg levels are associated with reduced all-cause mortality and graft failure in RTR. Kidney-derived hArg is likely to be of particular importance for proper maintenance of cardiovascular and renal systems.